Pharmaceutical Care Training Increases the Ability Pharmacists to Reduce the Incidence of Medication Error - Akrom Akrom; Budiyono Budiyono; Woro Supadmi (International Journal of Public Health Science (IJPHS), 2015)
The objective of the study was to know the potential incidence of medication errors before and after the training of pharmaceutical care in the Outpatient Pharmacy Unit of general privat hospital in rural area of Yogyakarta. The observational studi used to describe the potential medication errors in prescribing phase and dispensing phase and to determine its completion. This research was conducted prior to the training of pharmaceutical care that is in May and after the training of pharmaceutical care that was in June 2014 at the Outpatient Unit of general privat hospital in rural area Yogyakarta. The data was taken from a book review of prescriptions in outpatient units for the month. The results showed that the number of potential medication errors before the training of pharmaceutical care in prescribing phase (prescribing errors) found 17 cases or 0.21% and the dispensing phase (dispensing error) as many as 36 cases or 0.45%. While the potential for medication errors after the training phase of pharmaceutical care in prescribing phase (prescribing error) is found as many as 115 cases or 1.45% and the dispensing phase (dispensing error) is found as many as 165 cases or 2.10%.